Toll-like receptor 7/8 agonists stimulate plasmacytoid dendritic cells to initiate TH17-deviated acute contact dermatitis in human subjects - Garzorz-Stark, Natalie; Lauffer, Felix; Krause, Linda; Thomas, Jenny; Atenhan, Anne; Franz, Regina; Roenneberg, Sophie; Boehner, Alexander; Jargosch, Manja; Batra, Richa; Mueller, Nikola S.; Haak, Stefan; et al. (Journal of allergy and clinical immunology, 2018)
A standardized human model to study early pathogenic events in patients with psoriasis is missing. Activation of Toll-like receptor 7/8 by means of topical application of imiquimod is the most commonly used mouse model of psoriasis. We sought to investigate the potential of a human imiquimod patch test model to resemble human psoriasis. Imiquimod (Aldara 5% cream; 3M Pharmaceuticals, St Paul, Minn) was applied twice a week to the backs of volunteers (n = 18), and development of skin lesions was monitored over a period of 4 weeks. Consecutive biopsy specimens were taken for whole-genome expression analysis, histology, and T-cell isolation. Plasmacytoid dendritic cells (pDCs) were isolated from whole blood, stimulated with Toll-like receptor 7 agonist, and analyzed by means of extracellular flux analysis and real-time PCR. We demonstrate that imiquimod induces a monomorphic and self-limited inflammatory response in healthy subjects, as well as patients with psoriasis or eczema. The clinical and histologic phenotype, as well as the transcriptome, of imiquimod-induced inflammation in human skin resembles acute contact dermatitis rather than psoriasis. Nevertheless, the imiquimod model mimics the hallmarks of psoriasis. In contrast to classical contact dermatitis, in which myeloid dendritic cells sense haptens, pDCs are primary sensors of imiquimod. They respond with production of proinflammatory and TH17-skewing cytokines, resulting in a TH17 immune response with IL-23 as a key driver. In a proof-of-concept setting systemic treatment with ustekinumab diminished imiquimod-induced inflammation. In human subjects imiquimod induces contact dermatitis with the distinctive feature that pDCs are the primary sensors, leading to an IL-23/TH17 deviation. Despite these shortcomings, the human imiquimod model might be useful to investigate early pathogenic events and prove molecular concepts in patients with psoriasis. [Display omitted]